Student’s Perceptions and Challenges on English Club Extracurricular Activity at SMAN 8 Lubuklinggau - Desti Aryanti; Ardayati Ardayati; Hamdan Hamdan (Institut Nalanda, 2024)
This research aimed to identify and describe students’ perceptions and challenges on English Club Extracurricular Activity at SMAN 8 Lubuklinggau. The researcher used mixed method to conduct this research, the subjects of this research were all members of English club at SMAN 8 Lubuklinggau that consist of 28 members. The researcher used questionnaire to find out students’ perception and interview to find out students’ challenges. The results showed that most of students have positive perception toward English club activity at SMAN 8 Lubuklinggau. Since joined English Club, Students pronunciation is better and students add their English vocabularies step by step, students also more confident and more interested in learning English, English club also motivate the students to improve English skill. Aside from that, English club is one of a comfortable, fun and a better place that suitable for students to speak English, students also have more time to practice English through English Club. Besides that, the researcher also found there are several students' challenges in learning English on English Club extracurricular activity at SMAN 8 Lubuklinggau. These challenges categorized by two factors namely linguistics: lack of vocabulary, poor pronunciation, lack of grammar knowledge and not fluency. Non-linguistics: not confidence, feel afraid, less supported, nervous and less motivation.